Pendekatan Komunikasi Partisipatif dalam Pemberdayaan Peternak: Telaah Konseptual dan Studi Empiris - Nurhikmah, Elva Ahlia; Lazuardi, Muhammad Abrori; Sulistyati, Marina; Yunasaf, Unang (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The livestock sector plays a strategic role in agricultural development and improving community welfare, especially in developing countries such as Indonesia. However, small-scale farmers still face various challenges such as limited access to resources, lack of technical knowledge, and low adoption of modern technology. The top-down approach that has been applied in empowerment programmes is often ineffective because it places farmers in a passive role. This study aims to assess the effectiveness of participatory communication approaches in empowering farmers through a literature review using a descriptive-analytical approach. The findings indicate that participatory communication can increase technology adoption, livestock productivity, and programme sustainability through the strengthening of local capacity. Collaboration between farmers, extension workers, and researchers in the knowledge exchange process has proven to generate more contextual and applicable solutions. The success of this approach is greatly influenced by the quality of facilitators, institutional support, and community readiness. However, challenges such as knowledge gaps and resource constraints remain obstacles that need to be overcome. Thus, participatory communication is not only an extension method but also a crucial strategy in creating inclusive, needs-based, and sustainable farmer empowerment.